Water Consumption and Nursing Characteristics of Infants - Keith E. Heller, DDS, DrPH; Woosung Sohn, DDS, MS, PhD; Brian A. Burt, BDS, MPH, PhD; (2000)
The purpose of this project was to determine raciayethnic differences in water consumption levels and nursing habits of children younger than 2 years old